SOCIAL MEDIA JOURNALISM: MONETISASI BERITA DI YOUTUBE MELALUI NEWS VLOG PACKAGING - Putri, Melisa Indriana (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2021)
The rapid growth of technology has two dilemmatic implications for journalistic practice. Technology can support the dissemination of quality journalism. However, it also threatens its quality, especially when the quality of news is also measured by the quantity of the audience. Hence, the media industry explores the potentials to develop revenue streams. Nevertheless, the news also competes with the popularity and speed of social media at the same time. Monetization through YouTube as a practice of social media journalism is an opportunity. The synergy of the strength and characteristics of the YouTube platform with the creative process in news content packaging creates news vlog packaging, informative, attractive, and profitable. Keywords: News vlog, social media, journalism, YouTube, monetization.